Credit spreads and economic activity in eight European economies - Veleanu, Veronica (2013)
In this thesis we examine the relationship between corporate bond spreads and economic activity in eight European countries using data on 500 corporate bonds between July 1994 and May 2011 for the United Kingdom and between October 2001 and May 2011 for Austria, Belgium, France, Germany, Italy, Netherlands and Spain. We construct a unique dataset of corporate bond spreads from bond-level data employing a similar methodology to Gilchrist and Zakrajsek (2012a) in the United States. Thus, we ensure that our credit spread measure is not distorted by illiquidity, embedded options, or mismatched maturities and coupon schedules between the two bond instruments being compared. We evaluate the importance of the country-level corporate bond spread index in .predicting the future growth in real activity at the individual country level for various measures of economic activity (such as industrial production, unemployment available at monthly frequency; and employment and real GOP available at quarterly frequency). We find that the credit spread index is a consistent predictor of real activity even when we include measures of monetary policy tightness (such as the term spread and the real interest rate), other leading indicator variables (economic sentiment and consumer confidence) and factors extracted from a large macro dataset. Our results are consistent at different forecasting horizons and are robust to different measures of the credit spread index. We then decompose the credit spread by purging it of expected default, tax and liquidity premia in an attempt to determine what component accounts for its information Content. We find that the excess bond premium, an indicator of financial market tightness, is the major driving source of the spread's predictive content. When)He compare the predictive ability of the credit spread and the excess bond premium across individual countries within the Euro area and Outside the Euro area, we find that mainly the core European countries have similar predictive ability, while the other countries in the Euro area and the UK are more heterogeneous.